Association of Cytomegalovirus Infection in Preterm Infants and Neonatal Outcomes: A Matched Cohort Study - Lo, Emily; Shah, Prakesh S.; Chow, Jean; Stavel, Miroslav; Harabor, Andrei; Alvaro, Ruben; Augustine, Sajit; Banihani, Rudaina; Lee, Seungwoo; Rolnitsky, Asaph; on behalf of the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2025)
This study aimed to explore the association of cytomegalovirus (CMV) infection in preterm infants of ≤32 weeks' gestation and neonatal morbidities.This was a matched cohort study of preterm infants born between 22 and 32 weeks gestation age and <1,500 g in birth weight who were admitted to participating tertiary NICUs within the Canadian Neonatal Network between April 2009 and December 2018. Infants were randomly matched in a 1:4 ratio (73 CMV-positive to 292 CMV-nonpositive infants) based on gestational age (in weeks), sex, birth weight (± 50 g), and number of days of oxygen exposure within the first 28 days after birth (± 2 days). Neonatal morbidities were compared between the two groups using conditional logistic regression after adjustment of unmatched confounders.The CMV-positive infants were of lower median birth weight compared to CMV-nonpositive infants (722 vs. 743 g; p < 0.05). The duration of noninvasive respiratory support (59 vs. 43 days; p < 0.05), invasive respiratory support (35 vs. 24 days; p < 0.05), oxygen therapy (115 vs. 67 days; p < 0.05), and odds of bronchopulmonary dysplasia (BPD; 90% vs. 71%; adjusted odds ratio: 3.52 [1.54, 8.07]) were higher for CMV-positive infants compared to CMV-nonpositive infants. Other morbidities were not statistically significantly different.CMV infection in very preterm infants was associated with increased duration of oxygen and respiratory support and increased odds of BPD.
Keywords: preterm; bronchopulmonary dysplasia; chronic lung disease